2016
DOI: 10.1186/s12939-016-0383-z
|View full text |Cite
|
Sign up to set email alerts
|

Financial access to health care for older people in Cambodia: 10-year trends (2004-14) and determinants of catastrophic health expenses

Abstract: BackgroundOlder people make up an increasing proportion of the population in low- and middle-income countries. This brings a number of challenges, as their health needs are greater than, and different from, those of younger people. In general, these health systems are not geared to address their needs, and traditional support systems tend to erode, potentially causing financial hardship when accessing health care. This paper provides an overview of older Cambodians’ financial access to health care over time, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 24 publications
5
28
1
Order By: Relevance
“…Our results show that nearly 1% of households had experienced CHE in the overall sample and 4% of those who had done OOPs. These frequencies are well below those of other low-and middle-income countries [7,[20][21][22][23]. A low incidence of catastrophic payments could reflect the fact that people receive the care they need and are protected from direct payments.…”
Section: Discussionmentioning
confidence: 86%
“…Our results show that nearly 1% of households had experienced CHE in the overall sample and 4% of those who had done OOPs. These frequencies are well below those of other low-and middle-income countries [7,[20][21][22][23]. A low incidence of catastrophic payments could reflect the fact that people receive the care they need and are protected from direct payments.…”
Section: Discussionmentioning
confidence: 86%
“…The high cost of cancer treatment leads the elderly to incur higher healthcare costs because as is well known the treatment and medication for cancer is expensive compared to other diseases like hypertension, diabetes mellitus and cardiovascular disease. This situation can also cause the elderly to become trapped into CHE and poverty (Li et al 2012;Minh et al 2013;Li et al 2014); Jacobs et al (2016). Meanwhile, for hypertension, the negative sign at the 1% significance level showed that the disease had a lower impact compared to other diseases against the healthcare costs among the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…Due to financial hardship, living alone and having specific illnesses which require the utilisation of health care services, the elderly spend more on health expenditure compared to others and face the prospect of catastrophic health expenditure (Jacobs et al 2016;Yang et al 2016;Arsenijevic et al 2016). One study that investigated the socioeconomic and medical correlation of health expenditure among the rural elderly in South India was carried out by Brinda et al (2012).…”
Section: Abstrakmentioning
confidence: 99%
See 1 more Smart Citation
“…children younger than age five, and seniors aged 60+) were taken directly from 2019 population projections. Elderly are defined as people aged 60+ because there is Cambodia‐specific evidence indicating households with people older than age 59 are very vulnerable to out‐of‐pocket (OOP) health care expenditures (Jacobs, de Groot and Fernandez Antunes, ). Estimates for PLHIV and people with TB were sourced from the World Health Organization Global Health Observatory and the Yale Global Health Review ( YGHR , ), respectively.…”
Section: Data Methods and Limitationsmentioning
confidence: 99%